Motivation Is Deficient in the Spontaneously Hypertensive Rat (SHR), a Rodent Model of Adhd: Evidence from an Operant Breakpoint Paradigm - (:unkn) unknown (My University, 2019)
Attention Deficit Hyperactivity Disorder (ADHD) is one of the most commonly diagnosed childhood neurobehavioral disorders. ADHD is characterized by three core behavioral deficits (hyperactivity, inattention, and impulsivity) that significantly hinder the daily functioning of those diagnosed. Furthermore, children with ADHD have problems with motivation and often require larger, more frequent rewards in order to complete a task. In this study, we used the Spontaneously Hypertensive Rat (SHR), a rodent model of ADHD that exhibits all the core deficits of the disorder. The goal of the current study was to further validate the SHR as a model of ADHD by training rats in an operant conditioning breakpoint paradigm which is commonly used to assess motivation. Twelve male SHR and 12 male Wistar Kyoto (WKY) control rats were trained on a Progressive Ratio schedule that increased in difficulty until the rats reached their breakpoint, which was defined as the point at which the animals stopped working. The breakpoint served as a measure of motivation and the higher the breakpoint, the more motivated the animal was. Results show that the SHR animals had a significantly lower breakpoint compared to the control animals, indicating that the SHR animals gave up working on the task much sooner. While the etiology of the disorder is largely unknown, we do know that various areas of the brain, including the cerebellum, have abnormalities and warrants further investigation. In the current study, the dentate nucleus, one the three deep nuclei of the cerebellum, was examined as it has previously been shown to have a role in motivational behavior. Findings indicate that the dentate nucleus volume was smaller in the SHR animals compared to the same structure in WKY rats. It is proposed that the smaller dentate nucleus in SHR rats may contribute to the motivational deficits expressed in these animals.
Keywords: ADHD; Cerebellum; SHR